Blended learning research in Indonesia (2018–2023): A bibliometric analysis of trends, challenges, and opportunities - Hafwa, Arumi Madana Hafwa; Nafi'ah, Azmi Afifatun Nafi’ah; Teguh Arie, Sandy (Universitas Negeri Semarang, 2024)
The bibliometric analysis of blended learning research in Indonesia from 2018 to 2023 reveals a transformative landscape influenced by the COVID-19 pandemic. This study examines scientific production, thematic evolution, and research dynamics surrounding blended learning, utilizing advanced bibliometric techniques and visualization tools. The findings indicate a significant surge in publications during 2020–2021, reflecting the educational sector's rapid adaptation to unprecedented disruptions. Through comprehensive keyword network analysis and citation patterns, the study uncovers multidimensional perspectives on blended learning, emphasizing technological integration, pedagogical innovation, and socio-cultural considerations. The research highlights a complex interplay between technological advancements, educational methodologies, and systemic challenges. Furthermore, the study spans multiple disciplines, including social sciences, physics, computer science, and engineering, demonstrating the interdisciplinary nature of blended learning implementation. Despite remarkable progress, critical barriers persist, including limitations in digital infrastructure, unequal technological access, and inadequate educator preparedness. These challenges underscore the need for strategic interventions to enhance the effectiveness of blended learning. By providing nuanced insights into Indonesia’s evolving educational landscape, this analysis highlights both opportunities and obstacles in implementing blended learning strategies across diverse educational contexts.